Cortical bone and fracture risk: The Tromsø Study - Kral, Rita (Bone, 2018)
Background: The aim of this thesis was to explore the association of the cortical architecture of the proximal femoral shaft with non-vertebral fractures. We tested the hypotheses that: (i) cortical parameters are associated with fracture risk independent of Fracture Risk Assessment Tool (FRAX) or Garvan estimates, (ii) women with fractures that are unidentified by FRAX but identified by cortical porosity have a different patient profile that contributes to their fracture risk, and (iii) women with type-2 diabetes mellitus (T2DM) have lower bone turnover markers (BTMs) and lower cortical porosity than those without diabetes, and that higher serum glucose level and body mass index (BMI) are associated with lower BTMs and cortical porosity. Methods: We quantified FRAX and Garvan estimates with femoral neck areal bone mineral density (FN aBMD) and femoral subtrochanteric architecture in 211 postmenopausal women, aged 54–94 years, with non-vertebral fractures and 232 controls in a nested case-control study. Results: Paper I: Cortical porosity and thickness were associated with fracture risk independent of FRAX and Garvan estimates. Cortical porosity but not cortical thickness improved the net reclassification of fracture cases compared with FRAX alone but not compared with Garvan. Paper II: Fracture cases unidentified by FRAX but identified by cortical porosity had a patient profile different from fracture cases identified by FRAX. These patients were younger, had a higher FN aBMD, a lower FRAX score, and fewer had a prior fracture, they had higher cortical porosity, thinner cortices, and a larger total bone size than those identified by FRAX alone. Paper III: Women with T2DM had a higher serum glucose, BMI, and subtrochanteric total volumetric BMD but a lower cortical porosity than nondiabetic women. Increasing serum glucose level was associated with lower BTMs and cortical porosity. Increasing BMI was associated with lower BTMs and thicker cortices. Conclusion: These results suggest that cortical porosity was the ...